Condicionantes edáficas para a monodominância do gênero Peltogyne (Fabaceae) na Ilha de Maracá, Roraima, Norte da Amazônia brasileira - Villacorta, Carlos Darwin Angulo (2017)
Populations of monodominant forests of the genus Peltogyne (Fabaceae) occur naturally on the island of Maracá and adjacent areas, Roraima, northern of the Brazilian Amazon. This monodominant forest set has been associated to soils with high concentrations of magnesium (Mg). However, recent investigations with larger spatial coverage indicate that the environmental features that allow the occurrence of monodominance of this genus may be associated with other environmental conditions not related to Mg. Establishing a new paradigm for the monodominance of this genus in Maracá contributes to improve the compression of the ecological and evolutionary processes of the regional forest species. The objective of this study was to determine the environmental variables that determine the monodominance of the genus Peltogyne (P. gracilipes + P. paniculata) in forests of the northern ecoregion of Roraima. The topographic factors were evaluated based on the altitudinal gradient, as well as the physical and chemical characteristics of the soil to architect the environmental model that defines the monodominance of this genus. For this purpose, a forest inventory was carried out in 129 plots (10 m x 50 m each = 6.45 ha) distributed systematically in the eastern sector of Maracá Island. All arboreal individuals with diameter at breast height (DBH) ≥ 10 cm were inventoried and distinct in three groups: Palms (Arecaceae), Peltogyne (P. gracilipes + P. paniculata) and Other Trees (other arboreal individuals). Altitude, edaphic variables (texture and fertility) and macro characterization of drainage (poor or well drained) were observed in all sample plots. Non-metric multidimensional scaling (NMDS) techniques associated with linear regressions were used to investigate which variables best answer for the Peltogyne monodominance. Tree aboveground biomass (AGB) was used as descriptor of the composition and structure of each sample plot, being used as a dependent variable in the regression analysis. A total of 3068 individuals were observed, of which 292 belonged to the genus Peltogyne. The altitude differed significantly based on the plots with presence or absence of Peltogyne (t = 33.24 and p <0.00001), indicating that the highest abundance of this genus are preferentially found in low altitude environments associated with seasonal flooding. The use of linear regressions indicated that in addition to altitude (R2 = 0.34, p <0.00001), the high concentrations of Fe+2 (R2 = 0.31, p <0.00001) are also associated with the monodominance of Peltogyne response to the poorly drained soils. The predictive power of Mg was very low. The conclusion of this study is that the monodominance of Peltogyne in the eastern sector of the Maracá Island is associated with its tolerance to environments with high hydro-edaphic restrictions, dominated by poorly drained soils (low altitude and temporal anoxia) and high concentrations of Fe+2, where the role of Mg is secondary.